The validity of the notary's self-safety clause in the notary deed - Natalia Budiman; Ni Made Ayu Sekar Kinasig; Tang Monica Christina Pangandaheng; Aida Qothrin Nada (Jurnal Cakrawala Hukum, 2022)
The results of this study show that the self-security clauses listed by the notary in the deeds did not violate the provisions of laws and regulations, especially the UUJN. That is, the clause is validly stated on the condition that the notary lists the clause based on the statements of the complainants and that the statements or statements and supporting documents as a reference for making a notarial deed are valid, so if in the future it is known that there are wrong things, then the notary can use the clause as a form of effort to secure themselves or as a form of notarial resistance if the notary is used as a witness, the suspect/defendant, the defendant/co-defendant because of the deed he made. Juridically, the notary's self-protection clause does not have the legal force to bind third parties such as prosecutors, public prosecutors, or judges, so the clause cannot provide legal immunity for the notary if the notary can indeed be proven guilty in advance of the court. The clause only applies to notaries who have carried out the position's duties, especially in doing deeds by the provisions of the UUJN and laws and regulations.How to cite item: Budiman, N., Kinasig, N., Pangandaheng, T., Nada, A. (2022). The validity of the notary's self-safety clause in the notary deed. Jurnal Cakrawala Hukum, 13(3), 300-307. DOI:https://doi.org/10.26905/idjch.v13i3.8616.